2016
DOI: 10.3126/jnarc.v2i0.16120
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cropping for Raising Productivity and Farm Income of Small Farmers

Abstract: Multiple cropping is an agriculture system long adopted by marginalized small holder farmers especially in hills and mountains. This practice was a meant to enhance farm productivity when farming area is limited. Here, in this paper, a brief review on the benefits of multiple cropping is presented focusing on the practices adopted by marginalized farmers, in general. In multiple cropping, it is generally argued that the practice favors an efficient utilization of resources like air, water, light, space, and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
1
12
0
2
Order By: Relevance
“…The increased yield of clean coffee in the sole and staggered planting arrangement, it might be due to the increased population density of coffee trees, and the efficient utilization of the growth resources; viz., light, moisture, nutrients, etc. Similar result was observed in the previous works of Taye et al [40], Van der vossen [41], Hamdollah [42], Paudel [43], Mekonnen et al [44], Shamim and Mohammed [45]. They reported that the efficient utilization of the growth resources by the individual coffee plant could be the possible reason for the yield increment.…”
Section: Coffeesupporting
confidence: 89%
See 1 more Smart Citation
“…The increased yield of clean coffee in the sole and staggered planting arrangement, it might be due to the increased population density of coffee trees, and the efficient utilization of the growth resources; viz., light, moisture, nutrients, etc. Similar result was observed in the previous works of Taye et al [40], Van der vossen [41], Hamdollah [42], Paudel [43], Mekonnen et al [44], Shamim and Mohammed [45]. They reported that the efficient utilization of the growth resources by the individual coffee plant could be the possible reason for the yield increment.…”
Section: Coffeesupporting
confidence: 89%
“…In the pooled mean value, the highest yield advantage (0.82) was recorded similarly from the aforementioned treatment (Table 4). The higher yield advantage of the intercrops over the sole stand might be resulted from the compatibility of the component crops for efficiently utilization of the growth resources viz., light, moisture and nutrients [43,51,[53][54][55]. In addition, the result could be associated with the different root and shoot structures of coffee and enset plants, which results different competitive ability of the component crops for growth resource utilization [21,56].…”
Section: The Yield Advantage Of Coffeementioning
confidence: 99%
“…The rapid developments in protected cultivation and intensive cropping pattern have led to an increased index of multiple cropping [1,2]. The continuous cropping results in the deterioration of soil environment, serious diseases and pests attack on vegetables, and reduction of yield and quality of vegetable crops [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Another major use of hydropower plant is to link it with irrigation system and irrigate agriculture lands. As almost 70% land in Nepal is rain fed, production is uncertain [6]. When there is good monsoon rain there is good rice production that increases the country's Gross Domestic Product (GDP) and vice versa when poor monsoon [7] studied in Nepal and [8] studied in Ganges-Brahmaputra Basin of India regarding the rainfall variation.…”
Section: Irrigation and Drinkingmentioning
confidence: 99%